Pengaruh Layanan Paylater, Promo Gratis Ongkir, dan Flash Sale terhadap Keputusan Pembelian pada Konsumen Marketplace Lazada di Kabupaten Bandung - Meidin, Anzar; Sriyanto, Agus (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine the influence of Paylater Services, Free Shipping Promos, and Flash Sale on Purchase Decisions on Lazada marketplace consumers in Bandung Regency. Fierce competition between platforms such as Shopee, Tokopedia, Lazada, and Bukalapak encourages the development of various marketing strategies. This phenomenon is an interesting research object to examine how marketing strategies such as Paylater services, free shipping promos, and flash sales affect consumers' purchasing decisions on Lazada. This research is included in the type of quantitative research with the survey method. The population in this study is all Lazada consumers in Jelegong Village, Bandung Regency, who have made purchases and used or know about Paylater services, free shipping promos, and flash sales provided by Lazada. Data was collected using questionnaires that contained structured questions related to consumer perceptions and experiences. The research sample used a non-probability sampling technique with a purposive sampling approach, involving a total of 100 respondents who were considered representative. Data were analyzed with SPSS 22. The results of this study are that paylater services, free shipping promos, and flash sales affect purchase decisions. The results of this study show that Paylater Services, Free Shipping Promos, and Flash Sale partially have a positive and significant influence on Purchase Decisions. The Paylater Service variable (X1) has a strong correlation, Free Shipping Promo (X2) also shows a strong correlation, and Flash Sale (X3) has a very strong correlation with Purchase Decision (Y). Overall, these three independent variables significantly influenced consumers' purchasing decisions on Lazada, with a contribution of 76.3% to the purchase decision, while the remaining 23.7% were influenced by other variables outside of this study. This conclusion indicates that the marketing strategy is very effective in driving consumer purchase decisions on Lazada.